Determination of Salivary pH in Patients With Recurrent Aphthous Ulceration (RAU) - Abbass F Al-Taee; Ahmed S Khudhur (University of Mosul, College of Dentistry, 2010)
Aims: To determine salivary pH in patients with recurrent aphthous ulceration and in control normal subjects. Materials and Methods: A controlled clinical trial was performed on 60 subjects divided into 30 normal subjects and 30 patients with recurrent aphthous ulceration. The salivary pH was deter-mined using a chair-side pH meter. Results: Highly significant difference in pH level was observed between patients and control groups (t-value 5.420, p< 0.0001). There were no significant differences in pH levels between males and females in both patients and control groups. Conclusions: The pH of saliva in male patients with (RAU) was more toward acidic pH than normal male subjects.